2013
DOI: 10.1038/ki.2012.407
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infection–related glomerulonephritis in adults

Abstract: In the past, most cases of bacterial infection-related glomerulonephritis (IRGN) occurred in children following streptococcal upper respiratory tract or skin infections and were called postinfectious GN. Over the past 3 decades, there has been an important shift in epidemiology, bacteriology, and outcome of IRGN. A significant percentage of cases now target adults, particularly the elderly or immunocompromised. Because adult infections are often ongoing at the time of diagnosis, the term IRGN appears more appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
223
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(241 citation statements)
references
References 105 publications
12
223
1
5
Order By: Relevance
“…Nasr et al reported the following five characteristic criteria of infection-related glomerulonephritis: (1) clinical or laboratory evidence of infection preceding or at the onset of glomerulonephritis; (2) depressed serum complement; (3) endocapillary proliferative and exudative glomerulonephritis; (4) C3-dominant or co-dominant glomerular immunofluorescence staining; and (5) hump-shaped subepithelial deposits on electron microscopy. Of 86 patients with infection-related glomerulonephritis, 37 % fulfilled all five criteria, 41 % fulfilled 4 of the 5 criteria, and 22 % fulfilled 3 of the 5 criteria [13]. In the present patient, as shown in Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Nasr et al reported the following five characteristic criteria of infection-related glomerulonephritis: (1) clinical or laboratory evidence of infection preceding or at the onset of glomerulonephritis; (2) depressed serum complement; (3) endocapillary proliferative and exudative glomerulonephritis; (4) C3-dominant or co-dominant glomerular immunofluorescence staining; and (5) hump-shaped subepithelial deposits on electron microscopy. Of 86 patients with infection-related glomerulonephritis, 37 % fulfilled all five criteria, 41 % fulfilled 4 of the 5 criteria, and 22 % fulfilled 3 of the 5 criteria [13]. In the present patient, as shown in Fig.…”
Section: Discussionmentioning
confidence: 51%
“…A substantial number of cases now occur in adults, particularly the elderly, alcoholic persons, and patients who are immunocompromised. Because the presence of an infection is often ongoing at the time of renal biopsy, the term infectionrelated GN has been suggested as more appropriately describing this condition (6). In contrast to children, adults are more likely to have infection-related GN secondary to nonstreptococcal infections, particularly staphylococcal infection, and the overall prognosis in terms of renal and patient survival is poor.…”
Section: Discussion Of Questionmentioning
confidence: 99%
“…The most common extrarenal manifestation is congestive heart failure. 6,7 In contrast to PIGN, Streptococcus pyogenes is not a common cause of bacterial pericarditis. 8 A literature review revealed eight prior cases of purulent pericarditis caused by Streptococcus pyogenes and one case of constrictive pericarditis.…”
Section: Discussionmentioning
confidence: 99%